2005
DOI: 10.3168/jds.s0022-0302(05)72886-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parity and Supply of Rumen-Degraded and Undegraded Protein on Production and Nitrogen Balance in Holsteins

Abstract: Eight Holstein cows (4 primiparous and 4 multiparous) were used in a replicated 4 x 4 Latin square design to determine milk production response and N balance when diets had no NRC-predicted excess of rumen-undegradable protein (RUP) or rumen-degradable protein (RDP), 10% RUP excess, 10% RDP excess, or 10% excess of both RUP and RDP. Diets were fed as a total mixed ration with (dry matter basis) 25% alfalfa silage, 25% corn silage, 19 to 21% corn grain, and varying proportions of solvent soybean meal and expell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
7
20
1
Order By: Relevance
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 81%
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 81%
“…Assuming a volatilisation loss of 28% (Xiccato et al, 2005), 62.6 kg N are present in the manure management system. The value of 62.6 kg annual N excretion for buffaloes is substantially less than the value of around 85 kg reported for dairy cows (Flis and Wattiaux, 2005;Xiccato et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…Primiparous cows use some of their energy intake for growth (McDonald et al, 2002) and do not retain as much of additional nitrogen absorbed as multiparous cows do, resulting in more nitrogen excreted in the urine in primiparous cows when additional nitrogen is absorbed (Flis and Wattiaux, 2005). This suggests that primiparous cows have a smaller urea pool or a smaller demand to restore body protein mobilised earlier in lactation compared to multiparous cows (Flis and Wattiaux, 2005). In the model relating animal and feed factors to nitrogen efficiency by the dairy cows in this study, variation among cows, as a percentage of the total variation, in regard to nitrogen efficiency, were smaller for multiparous than for primiparous cows.…”
Section: Discussionmentioning
confidence: 89%